PRELIMINARY SCREENING OF PHYTOCHEMICAL CONSTITUENTS, ANTIOXIDANT AND ANTIMICROBICIDAL ACTIVITIES IN THE METHANOLIC LEAF EXTRACT OF COUROUPITA GUIANENSIS - ILANGOVAN, SUJATHA; P, THAVASUMANI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was the preliminary screening of the methanolic leaf extract of Couroupita guianensis for various phytochemical constituents, its antioxidant, antibacterial, and antifungal activities. Methods: Phytochemical screening of 18 qualitative, 6 quantitative constituents, antioxidant activity, alpha-amylase inhibitory activity, and alpha-glucosidase inhibitory activity of the methanolic extract of the leaf of C. guianensis was performed adopting the standard protocols. The disk diffusion methods were used for assessing the antibacterial and antifungal activities of the extract. Results: The preliminary studies revealed the presence of alkaloids, saponin, flavonoids, phenol, tannin, and terpenoids in the methanolic extract of the leaf of C. guianensis. Potent antioxidant, free radical scavenging activity, and inhibitory activity against α-amylase and α-glucosidase activity of the methanolic extract were also evident. Conclusions: The preliminary studies in the methanolic extract of the leaf of C. guianensis are suggestive of the therapeutic potentials of the methanolic extract of leaves of C. guianensis.